Effect of Biochar Application on Growth of Garden Pea (Pisum sativum L.) in Acidic Soils of Bule Woreda Gedeo Zone Southern Ethiopia - Tariku Berihun; Shiferaw Tolosa; Muluken Tadele; Firew Kebede (International Journal of Agronomy)
The aim of this experiment was to study the effect of types and rates of biochar on growth, yield, and yield component of garden pea at Bule wereda, Southern Ethiopia. The treatments consist of two types of biochar (corncobs and Lantana camara) and four rates of biochar (0, 6, 12, and 18 t ha−1). The experiment was laid out as a randomized complete block design in a factorial arrangement with three replications. Soil samples were collected at a depth of 0–30 cm and germination parameter and phonology of garden pea were recorded. The result showed that soil bulk density, porosity, pH, and exchangeable acidity were significantly (P<0.001) affected by biochar application. The result also showed that maximum germination percentage of garden pea seeds (95.23%) was recorded at 18 t ha−1 of Lantana biochar. The shoot length was significantly (P<0.05) affected at 15 days and 30 days of biochar application. Moreover, fresh shoot weight and dry root biomass, number of seeds per pod, and grain yield of garden pea were significantly affected (P<0.05). Of the substrate and application rate applied, Lantana camara 12 t ha−1 and Lantana camara 18 t ha−1 significantly increased yield of garden pea. Thus, further studies on effect of different biochars and their specific role are suggested to increase crop production.